Nonlinear Interactions in a Piezoceramic Bar Transducer Powered by a Vacuum Tube Generated by a Nonideal Source - Balthazar, José Manoel [UNESP]; Felix, J. L. Palacios [UNESP]; Brasil, R. M L R F; Krasnapolskaya, T. S.; Shyets, A. Yu. (Asme-amer Soc Mechanical Eng, 2009)
Interactions between the oscillations of piezoceramic transducer and the mechanism of as excitation-the generator of the electric current of limited power-supply-are analyzed in this paper In practical situations, the dynamics of the forcing function on a vibrating system cannot be considered as given a priori, and it must be taken as a consequence of the dynamics of the whole system. In other words, the forcing source has limited power as that provided by a dc motor for an example, and thus its own dynamics is influenced by that of the vibrating system being forced. This increases the number of degrees of freedom of the problem, and it is called a nonideal problem. In this work, we present certain phenomena as Sommerfeld effect, jump, saturation, and stability, through the influences of the parameters of the governing equations motion.
Keywords: averaging method; nonideal systems; Sommerfeld effect; saturation phenomenon